2012
DOI: 10.4236/jbbs.2012.22029
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Developmental Coordination Disorder: The Mirror Neuron System Hypothesis

Abstract: Primary impairments of developmental coordination disorder (DCD) include impairments in motor skill, motor learning, and imitation. Such difficulties present challenges for individuals with DCD and may persist into adulthood, negatively impacting daily life in school, work, and social domains. A better understanding of the neural correlates of motor and imitation impairments in DCD holds the potential for informing development of treatment approaches to address these impairments. Although the disorder is assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 112 publications
(173 reference statements)
0
20
0
3
Order By: Relevance
“…Some early studies have started to consider the neural mechanisms potentially implicated in DCD. These include, for example, whether potential mirror neuron deficits relate to dysfunction in the fronto-parietal system 18. However, the underlying neural processes remain unclear and the heterogeneous nature of the disorder further complicates attempts to find an underlying cause; hence, its aetiology remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Some early studies have started to consider the neural mechanisms potentially implicated in DCD. These include, for example, whether potential mirror neuron deficits relate to dysfunction in the fronto-parietal system 18. However, the underlying neural processes remain unclear and the heterogeneous nature of the disorder further complicates attempts to find an underlying cause; hence, its aetiology remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…). Earlier investigations have thus indicated that DCD may be related to a central nervous system pathology (Zwicker, Missiuna, & Boyd, 2009).…”
mentioning
confidence: 99%
“…& RODRIGUES, G.M. impairment) (WERNER et al, 2012), inabilidade física (physical awkwardness), disfunção da integração sensorial (sensory integrative dysfunction) (ZWICKER et al, 2012;WERNER et al, 2012), inabilidade congênita (congenital maladroitness) (CERMAK et al, 2002), disfunção neurológica menor (minor neurological dysfunction) e dano cerebral mínimo (minimal brain damage) (MAGALHÃES et al, 2011) e deficiência sensório-motora (sensory-motor impairment) (BONIFACCI, 2004).…”
Section: Resultados E Discussão 41 Histórico E Definiçãounclassified